EVALUASI PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS PADI GOGO (Oryza sativa L.) PADA BEBERAPA JARAK TANAM YANG BERBEDA - Fristy Rebecca Hasianta Sitohang; Luthfi Aziz Mahmud Siregar; Lollie Agustina P. Putri (Jurnal Agroekoteknologi, 2014)
Rice is an important commodity in Indonesia. As time went on the narrowing of fertile irrigatedland due to conversion of non-agricultural land for the benefit of making an effort to do that is theuse of improved varieties of upland rice using proper spacing. This study aims to determine themost appropriate spacing and varieties that will enhance the growth and production of uplandrice. The research was carried out on community lahan masyarakat 1 Tanjung Sari, District MedanMedan Selayang Municipal ± 25 m altitude above sea level in the month of June to October2012. This study uses a randomized block design (RBD) with treatment consisting of five varietiesof varieties namely, varieties Situ Bagendit, Situ Patenggang, Towuti, Batutegi and Cirata, andtreatment spacing of three that is 20x20 cm, 20x25 cm and 20x30 cm and the treatment wasrepeated three times.The data obtained were analyzed using analysis of variance, followed byDuncan's Multiple Range Test (DMRT). Results of data analysis showed that the different varietiesof real observations on variables plant height, number of tillers, number of panicles, number ofempty grains, the amount of productive grain, grain weight per sample, 1000 grain weight, and theweight per sample. Spacing is not significantly different on all variables observations. Interactionsbetween plant spacing and different varieties of real variables only on observations of productionper plot.Key words: varieties, spacing, upland rice.